Financial institutions under sanctions ("Journal "U". Economy. Management. Finance.", 2023)
The article is devoted to the definition of the existing problems of financial institutions in our country in the face of sanctions from Western countries. The negative dynamics in the number of banks in recent years and the trend towards the state concentration of bank capital have been determined.
Keywords: bank; finance; markets; sanctions